Hubungan Kepuasan dan Kepercayaan Mahasiswa Terhadap Lembaga Pendidikan Tinggi Dengan Keinginan Untuk Membujuk Calon Mahasiswa Melanjutkan Studi Ke Perguruan Tinggi - Zulganef Zulganef; Asfia Murni (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2008)
This main research goal is to provide a knowledge or information about west java market, especially higher educational institution consumer for foreign higher educational institutions whom have plan to reach Indonesia higher educational market. This research investigated the relations among satisfaction, trust, and intention to persuade student candidate to continue their education to higher education. This research shows that trust has a relationships with intention to persuade, and shows that trust is a consequence of learning process satisfaction and physical evidence satisfaction, but not a consequence of faculty satisafaction. The results shows that students of university would like to persuade students candidates if they are satisfied with learning process and physical evidence, and these satisfactions are the antecendent to trust, so that trust is an antecendent to intention to persuade